Setting up and running a paediatric emergency department in a hospital in Malawi: 15 years on. Issue 1 (21st June 2017) - Molyneux, Elizabeth M; Langton, Josephine; Njiram'madzi, Jenala; Robertson, Ann M
Abstract : Paediatric emergency care is not recognised as a specialty in many countries in Africa but is being practised increasingly. Setting up a paediatric emergency care unit takes time and often involves trial and error. Here we describe the start of the paediatric emergency department in Blantyre, Malawi, a low-income country and how it has continued to evolve over 15 years, in the hope that our experience will inform and assist others who are already developing their own emergency unit or wishing to do so.